Emerging evidence for FFLO states in layered organic superconductors (Review Article) - Beyer, R.; Wosnitza, J. (Физика низких температур, 2013)
In this short review, we report on the recently found growing experimental evidence for the existence of Fulde–Ferrell–Larkin–Ovchinnikov (FFLO) states in quasi-two-dimensional organic superconductors. At high magnetic fields aligned parallel to the conducting organic layers, we observe an upturn of the upper critical field beyond the Pauli limit, as evidenced by specific-heat and torque-magnetization measurements. Inside the superconducting state a second thermodynamic transition emerges. These features appear only in a very narrow angular region close to parallel-field orientation.